2020
DOI: 10.3126/jpahs.v7i2.31103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding COVID-19 among doctors and nurses at a tertiary care maternity hospital in Nepal

Abstract: Introduction: Knowledge, attitude, and practice (KAP) survey provides a suitable format to evaluate existing programs and to identify effective strategies for behavior change in society. This study aimed to investigate and compare KAP concerning COVID-19 among Health Care Professionals (HCPs) at Paropakar Maternity and Women’s Hospital (PMWH). Method: This was a cross sectional descriptive study conducted in HCPs (doctors and nurses) of PMWH, Nepal, from May to June 2020. A pre-validated questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…More than three fourth (76.5%) of the respondents strongly agreed that health care workers must update themselves about COVID-19, 57.4% strongly believed that WHO, CDC universal precautions could prevent COVID-19, 61.7% strongly agreed that information on COVID-19 should be disseminated among them, 60 % agreed active participation of health workers can reduce the prevalence of COVID-19, 42.6% strongly responded that intensive, emergency and symptomatic treatment should be given accordingly to COVID-19 patients and 78.3% of the respondents answered that PPE must be used when dealing with COVID-19 patients. These findings are in line with the results of similar research done at Paropakar Maternity and Women's Hospital, Kathmandu, Nepal (Ansari et al, 2020) and Vietnam (Huynh et al, 2020) that showed the majority of the respondents had positive attitudes on COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…More than three fourth (76.5%) of the respondents strongly agreed that health care workers must update themselves about COVID-19, 57.4% strongly believed that WHO, CDC universal precautions could prevent COVID-19, 61.7% strongly agreed that information on COVID-19 should be disseminated among them, 60 % agreed active participation of health workers can reduce the prevalence of COVID-19, 42.6% strongly responded that intensive, emergency and symptomatic treatment should be given accordingly to COVID-19 patients and 78.3% of the respondents answered that PPE must be used when dealing with COVID-19 patients. These findings are in line with the results of similar research done at Paropakar Maternity and Women's Hospital, Kathmandu, Nepal (Ansari et al, 2020) and Vietnam (Huynh et al, 2020) that showed the majority of the respondents had positive attitudes on COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, they also feared the transmission of disease in hospitals. Some studies showed an increase in 11,12 maternal mortality.…”
Section: Discussionmentioning
confidence: 99%